The Revolution Of Helix Theory: Transforming Public Policy - Resa Vio Vani; Zulyani, Eka Putri; Saputra, Deni; Ikhsan, Masrul (Bahasa Indonesia, 2024)
This research aims to analyze the urgency and impact of the helix theory revolution on transforming public policy. Using a comparative analysis method that includes bibliometric analysis and literature review, we examine various helix models: Triple Helix, Quadruple Helix, Quintuple Helix, Penta Helix, Open Innovation Helix, and Hexa Helix. The findings demonstrate that each model offers unique advantages in promoting innovation, inclusivity, and sustainability in public policy. The integration of diverse stakeholders such as universities, industry, government, civil society, media, and NGOs enhances policy responsiveness and effectiveness, addressing societal challenges holistically. Existing research on helix models primarily focuses on individual frameworks without comprehensive comparisons or evaluations of their cumulative impact on public policy. Additionally, there is limited exploration of the practical implementation and effectiveness of these models in various socio-economic contexts. This research addresses these gaps by providing a comparative analysis of multiple helix models and their collective influence on public policy transformation. The novelty of this research lies in its holistic approach to evaluating multiple helix models simultaneously, offering a comprehensive understanding of their comparative advantages and potential synergies. By integrating bibliometric analysis with an extensive literature review, this study provides new insights into how diverse stakeholder collaboration can enhance the innovation, inclusivity, and sustainability of public policies. This approach not only fills existing research gaps but also proposes a more integrated framework for policy-making in complex and dynamic environments